2 Corinthians - Minor, Mitzi, 1958- (Macon, Ga. : Smyth & Helwys Pub., 2009)
"Mitzi L. Minor's commentary on 2 Corinthians takes the reader deep into the thought world of Paul and his congregation at Corinth, exploring the social and theological tensions that shape Paul's relationship with the Corinthian Christians. His letter expresses his joy that prior severe correspondence had been positively received and addresses the issues that were tearing the church apart; for one, false teachers who were sowing discord and maligning Paul's character. Paul finds as well that many Corinthian Christians have repented of their rebellion, and he encourages them even as he seeks to vindicate his apostleship to those who challenged him.Minor encourages the reader imaginatively to enter the radically new ekklesia that was the earliest Church, not a body of like-minded and similarly stationed citizens, but a novel collective of diverse people and interests, never joined before, struggling together to discover the ways of God in a world completely overturned by the advent of Christ...the primary goal of the Smyth & Helwys Bible Commentary series is to make available serious, credible biblical scholarship in an accessible and less intimidating format. A visual generation of believers deserves a commentary series that contains not only the all-important textual commentary on Scripture, but images, photographs, maps, works of fine art, and drawings that bring the text to life. Each volume of the Smyth & Helwys Bible Commentary series features a CD-ROM, which expands the uses and capabilities of the Commentary even more" -- From publisher description.
Introduction -- Greeting and prayer : the fourth letter begins : 2 Cor. 1:1-11 -- The body of the letter begins : the issues surface : 2 Cor. 1:12-2:13 -- Paul's defense of his ministry and himself : 2 Cor. 2:14-7:4 -- The one who is led captive : 2 Cor. 2:14-3:6 -- Slave of the glorious ministry of the Spirit : 2 Cor. 3:7-4:6 -- The clay jar : 2 Cor. 4:7-5:10 -- Ambassadors of the ministry of reconciliation : 2 Cor. 5:11-6:10 -- Therefore-- : 2 Cor. 6:11-7:4 -- So, the issues are settled? : 2 Cor. 7:5-16 -- Titus brings consolation : 2 Cor. 7:5-16 -- The issues are not settled : 2 Cor. 8:1-9:15 -- Grace and the Jerusalem collection : 2 Cor. 8:1-5 -- The delegation to work on the collection : 2 Cor. 8:16-24 -- Grace and partnership (not patronage) through the Jerusalem collection : 2 Cor. 9:1-15 -- Things get worse : a new letter and a showdown visit : 2 Cor. 10:1-13:14 -- Introduction to chapters 10-13 : 2 Cor. 10-13 -- The third visit : bold authority for building up : 2 Cor. 10:1-11 -- Standard of measure : 2 Cor. 10:12-18 -- Refusing patronage : 2 Cor. 11:1-15 -- Boasting in weakness : 2 Cor. 11:16-12:13 -- The third visit : proving themselves : 2 Cor. 12:14-13:10 -- Farewell, and our concluding thoughts : 2 Cor. 13:11-14.
Includes bibliographical references (p. [259]-262) and indexes.
Print version record.
Keywords: Bible. -- Commentaries; Bible; RELIGION / Biblical Studies / New Testament; RELIGION / Biblical Studies / Paul's Letters; Commentaries; Electronic books